2014
DOI: 10.1080/ac.69.4.3036653
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dipyridamole stress echocardiography on galectin-3, amino-terminal B-type natriuretic peptide (NT-proBNP) and high-sensitivity troponin T

Abstract: Dipyridamole stress testing did not trigger clinically meaningful injuries to the myocardium. Galectin-3 testing may hence be preliminarily regarded as a complementary means for enhancing the diagnostic value of provocative testing. It is also worthwhile investigating whether patients with abnormal response to a provocative test and increased galectin-3 values may be targeted with specific therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…48 Our findings in the DIP group are consistent with previously published studies showing no hsTnT release following a dipyridamole challenge, which is probably due to the absence of adrenergic stimulation and resulting increased wall stress observed during the ExSE and DSE. 15,16,49,50…”
Section: Discussionmentioning
confidence: 99%
“…48 Our findings in the DIP group are consistent with previously published studies showing no hsTnT release following a dipyridamole challenge, which is probably due to the absence of adrenergic stimulation and resulting increased wall stress observed during the ExSE and DSE. 15,16,49,50…”
Section: Discussionmentioning
confidence: 99%
“…GAL-3 is a marker of tissue fibrosis, which is a hallmark of cardiac remodeling and heart failure. This can be reliably measured in the blood and studies have shown its prognostic value in heart failure [118]. GAL-3 is a 31-kDa member of family of lectins that bind beta-galactosides by either N-linked or O-linked glycosylation through their carbohydrate recognition domain (CRD) [119].…”
Section: Galectin-3 (Gal-3)mentioning
confidence: 99%
“…This biomarker can reliably be measured in the circulation, and several recent studies have shown its prognostic value in acute and chronic HF, and its potential utility in the general population (10). GAL-3 [also occasionally referred as Mac-2 or carbohydrate-binding protein (CBP)-35] is a 31-kDa member of a growing family of lectins that bind β-galactosides by either N-linked or O-linked glycosylation through their carbohydrate recognition domain (CRD) (11).…”
Section: Gal-3mentioning
confidence: 99%